Why Do Women Not to Go for Abortion in a Designated Legal Abortion Facility in Transkei Region of South Africa? - BL Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The implementation of choice arising from the Termination of Pregnancy Act of 1996 (Act 92 of 1996) is a challenge in South Africa as there are many abortions that are still carried out by illegal abortionists in the Transkei region. This raises the serious question as to why the women do not prefer to go instead to a designated legal abortion clinic which carries out safe abortions in South Africa.Objective: To study the underlying factors which prevent women from going for an abortion to designated legal abortion facilities.Method: This qualitative research was carried out by medical students who visited both the legal and illegal facilities in Mthatha in 2015 for their assignment during the rotation of their subject of speciality.Result: The legal clinics are not user-friendly, the staff misbehave with the girls, they cast doubt on their confidentiality, and they take a long time to do the abortions, while the illegal abortionists charge money for their services but they are quick and keep confidentiality.Conclusion: Legal abortion clinics are not user friendly.